2018
DOI: 10.1371/journal.pgen.1007601
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide meta-analysis of 158,000 individuals of European ancestry identifies three loci associated with chronic back pain

Abstract: Back pain is the #1 cause of years lived with disability worldwide, yet surprisingly little is known regarding the biology underlying this symptom. We conducted a genome-wide association study (GWAS) meta-analysis of chronic back pain (CBP). Adults of European ancestry were included from 15 cohorts in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium, and from the UK Biobank interim data release. CBP cases were defined as those reporting back pain present for ≥3–6 months; non… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(114 citation statements)
references
References 74 publications
4
93
1
Order By: Relevance
“…The analgesic effect of opioids might explain the positive association between chronic pain and opioid cessation. In addition, the Netrin-1 receptor gene, DCC, was related to chronic opioid exposure and chronic back pain in both mice and human studies [73,74].…”
Section: Discussionmentioning
confidence: 99%
“…The analgesic effect of opioids might explain the positive association between chronic pain and opioid cessation. In addition, the Netrin-1 receptor gene, DCC, was related to chronic opioid exposure and chronic back pain in both mice and human studies [73,74].…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide SNP Heritability was calculated using LDSC. We transformed the h 2 estimate from observed to liability scale using prevalence estimates of our sample (73%) and a population prevalence of 50 % [12,23,30,51,53,75,85,86,91,92] using the commands --samp-prev 0.73 and -- pop-prev 0.5. The liability scale heritability corrects for ascertainment bias regarding the prevalence of the condition.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence for the role of genetic factors in CP comes from twin and family studies [38] where its heritability is estimated to be as high as 60% [11,37]. More recently, large-scale genome-wide association studies (GWAS) have identified multiple genetic variants associated with chronic back pain [25,75] and multisite chronic pain [36] as further evidence of a genetic contribution to CP. However, their causal relationship has yet to be adequately examined.…”
Section: Introductionmentioning
confidence: 99%
“…Another significant CBP-associated gene variant is the lead SNP rs4384683, an intronic variant in the gene DCC (deleted in colorectal carcinoma) [21]. Netrin-1 is an axonal guidance molecule, and as such, participates in the development of cortical and spinal commissural neurons.…”
Section: (Deleted In Colorectal Carcinoma)mentioning
confidence: 99%
“…Neurovascular ingrowth into the IVD may be mediated by netrin-1 and DCC, which is a mechanism that has long been implicated in chronic discogenic back pain [25,26]. Given the phenotypic correlation between CBP and depression [27], the correlation between CBP and DCC (depressive symptoms associated with cross phenotype of rs4384683) could also be explained by pleiotropy [21]. In animal models of mechanical allodynia, interactions of Netrin1/DCC have been found to impact pain processing in the spinal cord [23].…”
Section: (Deleted In Colorectal Carcinoma)mentioning
confidence: 99%